Questions & Answers

Question

Answers

3y(2y-7) - 3(y-4) - 63 for y = -2.

Answer

Verified

128.4k+ views

The given algebraic expression is $3y(2y-7) - 3(y-4) – 63$

To simplify, we will first open the bracket.

So, the given expression can be written as:

$3y(2y-7) - 3(y-4) – 63 =6{y^2} - 21y - 3y + 12 - 63$ ---------(1)

On taking the terms of same power together and then adding them, we get:

$6{y^2} - 24y - 51 = 0$ . -------------(2)

So, this is a simplified form of the given expression. The expression is in terms of variable ’y’. The degree of this expression is 2.

Now, we will find the value of the simplified expression at $y =2$.

Putting y = 2 in equation 2, we get:

$6 \times {(2)^2} - 24 \times 2 - 51$

On further solving the above expression, we get:

$6 \times {(2)^2} - 24 \times 2 - 51 = 6 \times 4 - 48 - 51 = 24 – 99 = -75$

B= Bracket

O= of

D= Division

M= Multiplication

A = addition

S =subtraction